ANALISIS USAHA DAN PROSPEK BUDIDAYA JAHE GAJAH (Zingiber officinale) DI DESA KEMU KECAMATAN PULAU BERINGIN, KABUPATEN OKU SELATAN - Muridin (Jurnal Bakti Agribisnis, 2019)
Business Analysis and Prospect of Plant Cultivation Elephant Ginger (Zingiber officinale R) in Desa Beringin Island Kemu District of South OKU District. The purpose of this study was to calculate the amount of income and financial feasibility of farming ginger in Desa Beringin Island Kemu District of South OKU District. The choice of location is done intentionally (purposive) conducted in October 2015. Sampling was done by using purposive sampling method on 20 samples of 100 population who undertake the cultivation of ginger in the village Kemu with the criteria of the respondents had sought cultivation of ginger> 5 years and wide land> M².Hasil 1000 study showed that the total cost of production dikelu arkan in the cultivation of ginger in one cropping cycle (9 months) in 2015 amounted to Rp 14,834,059, total receipts amounted to Rp 39.222188 so that the total income received amounted Rp 24,388,128. NPV is Rp 19,211,923, IRR amounted to 54.54% and the Net B / C was 1.9 indicating that the cultivation of ginger in Desa Beringin Island Kemu District of South OKU District feasible (feasible) to be developed so it has good prospects in the future to be developed.